Analisis Perbedaan Tingkat Authentic Happiness Ditinjau Dari Jenis Kelamin Pada Dewasa Madya Di Kelurahan Kalianyar - Putri Tsalsabillah; Fatma Nofriza (Journal on Education, 2024)
This background is based on the emergence of a phenomenon in middle adulthood, where individuals adjust themselves independently to life and social expectations. Usually, men and women experience their happiest years in middle adulthood, a period which is also known as a period of crisis (generativity) and generally this phase is the period when men and women reach the peak of their happiness. Finding out whether men and women experience different levels of happiness in middle adulthood is the main aim of this research. With a sample size of 2,300 people, this research used comparative quantitative methodology. Because the study topic or data source is very broad, cluster sampling is used, namely the sample determination method. Therefore, certain population areas are used as the basis for sampling. The sample taken was 100 respondents, namely, 50 middle-aged men and 50 middle-aged women who were the samples for this study. Therefore, the level of happiness in middle adulthood does not differ significantly between men and women.